Given that
r = 1 ∑ ∞ r 2 1 = 6 π 2 ,
Evaluate the sum
r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 .
Note: Do NOT use WolframAlpha.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
tell me about 1st equation
I did the same.
the another method for this is Mitaz Leffer Form
Can any one tell me what if we make that substitution "X=2r+1" we will have the summation "1/x^2" from "1-->infinity" that result in "pi^2/6" ???
I arrived to the solution exactly as Sudeep did, beautiful.. =0)
I have a slightly harder generalization of this sum. Show that all non-trivial zeros of the complex interpolation of a function, say ζ ( s ) = ∑ n = 1 ∞ n s 1 , occur where ℜ ( s ) = 2 1 .
Yes, just slightly harder ....
Just a little bit harder. xD
seriesSum(1/(r^2) ,r,1,infinity) = pi^2 /6. = 1+1/4+1/9+1/16+1/25+1/36+1/49+...... Since 2r+1 is odd, seriesSum(1/(2r+1)^2 ,r,0, infinity) = 1+1/9+1/25+1/49+....... = pi^2/6 - 1/4-1/16-1/36-1/64-......= = pi^2 /6 -seriesSum(1/(2r)^2 ,r,1,infinity) = pi^2 /6 -1/4 * seriesSum(1/r^2 ,r,1,infinity) = pi^2 /6 - pi^2 /24 = pi^2 /8 =1.2337005501362.
Problem Loading...
Note Loading...
Set Loading...
Consider the sum, ζ ( 2 ) = r = 1 ∑ ∞ r 2 1
r = 1 ∑ ∞ r 2 1 = r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 + r = 1 ∑ ∞ ( 2 r ) 2 1
r = 1 ∑ ∞ r 2 1 = r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 + 4 1 ( r = 1 ∑ ∞ r 2 1 )
⇒ r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 = 4 3 ( r = 1 ∑ ∞ r 2 1 )
⇒ r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 = 4 3 × ζ ( 2 )
⇒ r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 = 4 3 × 6 π 2
⇒ r = 0 ∑ ∞ ( 2 r + 1 ) 2 1 = 8 π 2 = 1 . 2 3 3 7